2006
DOI: 10.1063/1.2401040
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical band energetics of Ba(M0.5Sn0.5)O3 for solar photoactive applications

Abstract: We report here a comparative study of the theoretically calculated electronic structures of cubic BaSnO3 and cubic Ba(M0.5Sn0.5)O3 with M=Ti, V, Cr, Zr, Ce, and Pb, the tetravalent metal ions, to explore their possible efficacy for the visible light photocatalysis and solar energy conversion. We performed the calculations within the framework of density functional theory by using WIEN97 code. The 3d orbitals of Ti, V, and Cr, 4d of Zr, and the 4f and 6s orbitals of Ce and Pb, respectively, contributed to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…It is an ntype semiconductor with a band gap of 3.1 eV as desired for materials to be employed as gas sensors [1]. Borse et al [2] were able to show that BaSnO 3 -based systems could be promising candidates for photocatalytic applications. Mizoguchi et al [3] reported that BaSnO 3 exhibits strong near-infrared luminescence at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an ntype semiconductor with a band gap of 3.1 eV as desired for materials to be employed as gas sensors [1]. Borse et al [2] were able to show that BaSnO 3 -based systems could be promising candidates for photocatalytic applications. Mizoguchi et al [3] reported that BaSnO 3 exhibits strong near-infrared luminescence at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…After filtering, washing and drying, the precipitate was calcined at 1050 • C for 3 h. Cerda et al [8] prepared the compound by adopting a modified version of the sol-gel technique. The mixed solutions of Ba(OH) 2 and K 2 SnO 3 · 3H 2 O were stirred vigorously, and after evaporation a xerogel of composition BaSnO 3 · 2H 2 O was obtained and finally calcined for 8 h at high temperature (1200-1400 • C). The hydrothermal synthesis of BaSnO 3 was accomplished [9] by adding ammonia to SnCl 4 hydrate to obtain the gel SnO 2 · xH 2 O which was suspended in aqueous Ba(OH) 2 until a metal ratio Ba/ Sn = 1.0 was attained.…”
Section: Introductionmentioning
confidence: 99%
“…This drawback may be overcome by the use of nanostructured materials, as reported by Moshtaghi et al 8,9 , who attained a high activity in the photodegradation of organic dyes. A high activity may also be attained, using the perovskite ability to form solid solutions resulting in defects, which can therefore improve its photocatalytic properties [10][11][12] . For instance, the solid solution BaSn 0.2 Pb 0.…”
Section: Introductionmentioning
confidence: 99%
“…The physico-chemical property of any material system is mainly determined by its lattice structure, which in turns determines their optical, electrical and magnetic properties [1,2]. The photocatalysts require certain stringent requirements with respect to the optical and electrical behavior of the constituent material.…”
Section: Introductionmentioning
confidence: 99%